Assessment of mental health of work from home employee due to movement control order / Duan Jin - Duan, Jin (2021)
The emergence of COVID-19 has crossed the borders at a speedy rate and has infected more than 80 million people from the worldwide. The emergence of lockdown and new norms has drawn the public's attention to the economic recession and lifestyle changes. However, the public neglected their mental health at the same time. At the early stage of the Movement Control Order (MCO), we conducted a pre-survey on the psychosocial hazards faced resulted from work from home concept during the MCO. Among the responds collected from 67 respondents, the most feedbacks obtained are 89.55% of respondents complained their working environment at home is poor and not suitable for long hours of working while 67.16% of them complained that their psychosocial issues arise from working alone at home for long hours and lack of social events. 44.78% of respondents complained that household chores and disruption from family members make them mentally stressed. As for mental stress, ZUNG Anxiety Self-Assessment scale was used to assess the employees’ anxiety level and the psychosocial safety climate was introduced to assess employees’ satisfaction towards their employers. The questionnaire was given out through an online platform and 95 responds were collected. According to the data analysis by SPSS software, we found that anxious symptoms do occur through participants. The most vulnerable group was assigned to the female employee, an employee with bigger household size and higher education level among our analysis. To improve employees' mental health, the employer can pay more effort towards these vulnerable groups in psychosocial safety climate perspective by enhancing organization participation and involvement.